ANALISIS TEMA CINTA DALAM NOVEL NEW MOON KARYA STEPHANIE MEYER - BULAMEI, IMELDA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
The novel New Moon which was written by Sthepenie Meyer tells about the romantic story of Isabella Swan with the two myth creatures which are Edward Cullen the vampire man and Jacob Black the werewolf. This research entitled ?Analisis Tema Cinta dalam Novel New Moon karya Stephenie Meyer?. The aims at identifying, describing and analyzing the love theme of this novel. The method of this research is intrinsic approach. Intrinsic approach is used through the plot, character and setting to identify and describe the love theme of the novel. The result of this research reveals that human beings really need love and friends, and love need courageous, caring and understanding to overcome the problems and start a happy life. New Moon explores different kinds of love. Apart from Bella?s one true romantic love for Edward, there is her loving friendship for Jacob who healed her pain after Edward left. Jacob, on the other hand, has romantic feelings for Bella, but accepts her friendship, hoping that Bella might be ready for something more in the future.